Gallay, Ed., Voices Of The Old South - Eyewitness Accounts, 1528-1861 - Vaughn, William (Teaching History: A Journal of Methods, 1995)
Voices of the Old South, ably edited by Alan Gallay of Western Washington University, ought to be a boon to all historians teaching upper-division and graduate-level courses in the history of the antebellum American South. As the dust jacket commentary observes, ’’Unlike many works in the Old South, which tend to focus on the immediate pre-war years, this volume gives equal attention to the sixteenth, seventeenth, and eighteenth centuries. Its geographic definition of the region is notably broad …. "